The incorporation of MALDI mass spectrometry imaging in studies to identify markers of toxicity following in utero opioid exposures in mouse fetuses - Barnette, Dustyn; Inselman, Amy L.; Kaldhone, Pravin; Lee, Grace S.; Davis, Kelly; Sarkar, Sumit; Malhi, Pritpal; Fisher, J. Edward; Hanig, Joseph P.; Beger, Richard D.; Jones, E. Ellen (Frontiers in Toxicology, 2024)
IntroductionIn 2015, the FDA released a Drug Safety Communication regarding a possible link between opioid exposure during early pregnancy and an increased risk of fetal neural tube defects (NTDs). At the time, the indications for opioid use during pregnancy were not changed due to incomplete maternal toxicity data and limitations in human and animal studies. To assess these knowledge gaps, largescale animal studies are ongoing; however, state-of-the-art technologies have emerged as promising tools to assess otherwise non-standard endpoints. Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) is a dynamic approach capable of generating 2D ion images to visualize the distribution of an analyte of interest across a tissue section.MethodsGiven the importance of lipid metabolism and neurotransmitters in the developing central nervous system, this study incorporates MALDI MSI to assess lipid distributions across mouse gestational day (GD) 18 fetuses, with and without observable NTDs following maternal exposure on GD 8 to morphine (400 mg/kg BW) or the NTD positive control valproic acid (VPA) (500 mg/kg BW).ResultsAnalysis of whole-body mouse fetuses revealed differential lipid distributions localized mainly in the brain and spinal cord, which included several phosphatidylcholine (PC) species such as PCs 34:1, 34:0, and 36:2 localized to the cortex or hippocampus and lyso PC 16:0 across all brain regions. Overall, differential lipids increased in with maternal morphine and VPA exposure. Neurotransmitter distributions across the brain using FMP-10 derivatizing agent were also assessed, revealing morphine-specific changes.DiscussionThe observed differential glycerophospholipid distributions in relation to treatment and NTD development in mouse fetuses provide potential targets for further investigation of molecular mechanisms of opioid-related developmental effects. Overall, these findings support the feasibility of incorporating MALDI MSI to assess non-standard endpoints of opioid exposure during gestation.